2023
DOI: 10.4103/jmau.jmau_64_21
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblasts in odontogenic cysts and tumors: An immunohistochemical study

Abstract: Objective: The objective of this study was to assess immunohistochemically the presence of myofibroblasts both qualitatively and quantitatively in odontogenic cysts and tumors and to compare with the control cases of squamous cell carcinoma and to correlate the results with biologic behavior of these lesions. Materials and Methodology: Formalin-fixed, paraffin-embedded blocks of odontogenic cysts and tumors were retrieved from institutional archives. The sample size is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…MFs are differentiated broblasts that express α-SMA and have intermediate characteristics between conventional broblasts and smooth muscle cells [30] being able to remodel and degrade the extracellular matrix by secreting matrix metalloproteinases, driving the invasive growth of lesions odontogenic cyst [31]. The few studies that investigated the presence of MFs in odontogenic lesions suggest that the increase in the number of these cells contributes to the progression of the lesion and more aggressive biological behavior [13,17,21,24,25,32,33]. Anusai et al [10] reported that epithelial and stromal cell interactions are fundamental in controlling the growth and clinical behavior of odontogenic cystic lesions and that MFs are seen in greater numbers in OKC than in DC.…”
Section: Discussionmentioning
confidence: 99%
“…MFs are differentiated broblasts that express α-SMA and have intermediate characteristics between conventional broblasts and smooth muscle cells [30] being able to remodel and degrade the extracellular matrix by secreting matrix metalloproteinases, driving the invasive growth of lesions odontogenic cyst [31]. The few studies that investigated the presence of MFs in odontogenic lesions suggest that the increase in the number of these cells contributes to the progression of the lesion and more aggressive biological behavior [13,17,21,24,25,32,33]. Anusai et al [10] reported that epithelial and stromal cell interactions are fundamental in controlling the growth and clinical behavior of odontogenic cystic lesions and that MFs are seen in greater numbers in OKC than in DC.…”
Section: Discussionmentioning
confidence: 99%
“…MFs são fibroblastos diferenciados que expressam α-SMA e possuem características intermediárias entre fibroblastos convencionais e células musculares lisas (Hinz, 2020) sendo capazes de remodelar e degradar a matriz extracelular por meio da secreção de metaloproteínases da matriz, conduzindo o crescimento invasivo de lesões císticas odontogênicas (Roy e Gard, 2013). Os poucos estudos que investigaram a presença de MFs em lesões odontogênicas sugerem que o aumento no número dessas células contribui para a progressão da lesão e comportamento biológico mais agressivo (Vered et al, 2005;Nadalin et al, 2012;Syamala et al, 2016;Dandena et al, 2017;Santos et al, 2017;Pereira et al, 2018;Pinisetti;Tadi;Manyam, 2022). A vimentina é um filamento intermediário de classe II expresso principalmente no tecido mesenquimal (Sudhakara et al, 2016).…”
Section: Discussionunclassified